2015
DOI: 10.1080/15582159.2015.998964
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Qualifications and Productivity in Secondary Schools

Abstract: This study examined the relationship between observable teacher characteristics and productivity as measured by an increase in student achievement on a standardized test using a value-added approach. This analysis focused on teachers of algebra, geometry, and 11th grade English Language Arts in Arkansas. The authors generated a value-added score at the school-course level and attributed that score to each teacher of that course in the school. The authors then regressed observable teacher characteristics on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
11
1
1
Order By: Relevance
“…For instance, some studies have found the relationship between advanced degree and student achievement to be positive (Betts, Zau, & Rice, ; Dee, ; Nye, Konstantopoulos, & Hedges, ). In contrast, other studies have found that relationship to be insignificant (Aaronson, Barrow, & Sander, ; Shuls & Trivitt, ; Winters, Dixon, & Greene, ) or even negative (Clotfelter, Ladd, & Vigdor, ).…”
Section: Introductionmentioning
confidence: 79%
“…For instance, some studies have found the relationship between advanced degree and student achievement to be positive (Betts, Zau, & Rice, ; Dee, ; Nye, Konstantopoulos, & Hedges, ). In contrast, other studies have found that relationship to be insignificant (Aaronson, Barrow, & Sander, ; Shuls & Trivitt, ; Winters, Dixon, & Greene, ) or even negative (Clotfelter, Ladd, & Vigdor, ).…”
Section: Introductionmentioning
confidence: 79%
“…Okul yöneticileri mesleki yeterlik, kişisel özellikler ve örgütsel bağlılığa odaklanmaktadırlar. Bu bulgular, okul yöneticilerinin bilişsel kurgularının daha önce Çalışkan, Işık ve Saygın (2013), Darling-Hammond (2000), Gençtürk, Akbaş ve Kaymakçı (2012) ve Shuls ve Trivitt (2015) tarafından yürütülen araştırmaların bulguları ile tutarlı olduğunu göstermektedir. Başka bir ifadeyle, bu sonuçlar okul yöneticilerinin ideal öğretmen niteliklerine ilişkin doğru bilişsel kurgulara sahip olduklarını göstermektedir.…”
Section: Discussionunclassified
“…The impact of passing a licensure exam on student achievement is estimated in the second model. This strategy has been used by Shuls and Trivitt (2015a, 2015b).…”
Section: Methodsmentioning
confidence: 99%
“…Many have examined the relationship between teacher licensure exams and teacher quality (Clotfelter, Ladd, & Vigdor, 2006, 2010; Goldhaber, 2007; Shuls & Trivitt, 2015a, 2015b, etc.). Each of these studies use large administrative datasets from state departments of education in North Carolina (Clotfelter et al, 2006, 2010; Goldhaber, 2007) and Arkansas (Shuls & Trivitt, 2015a, 2015b). These analyses measured teacher quality in terms of value-added student achievement as measured by standardized exams.…”
Section: Literature Reviewmentioning
confidence: 99%